2009
DOI: 10.1111/j.1475-6765.2008.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

Governments and unpopular social policy reform: Biting the bullet or steering clear?

Abstract: Abstract. Under which conditions and to what extent do governments pursue unpopular social policy reforms for which they might be punished in the next election? This article shows that there exists substantial cross-cabinet variation in the degree to which governments take unpopular measures and argues that current studies cannot adequately explain this variation. Using insights from prospect theory, a psychological theory of choice under risk, this study hypothesises that governments only engage in unpopular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 67 publications
4
81
1
1
Order By: Relevance
“…In this context, BAB is considered as a way to circumvent electoral punishment by influencing steps (2) and (3) (Hinterleitner, 2015). Scholars have examined the use of blame avoidance strategies for retrenchment purposes in various settings and have explored the conditions under which officeholders can successfully apply such strategies (Vis, 2009;Giger and Nelson, 2011;Wenzelburger, 2011;Mortensen, 2012;Jensen and Mortensen, 2014;Wenzelburger, 2014;Vis, 2016;Hinterleitner et al, 2016;Sager and Hinterleitner, 2016).…”
Section: Four Worlds Of Blame Avoidancementioning
confidence: 99%
“…In this context, BAB is considered as a way to circumvent electoral punishment by influencing steps (2) and (3) (Hinterleitner, 2015). Scholars have examined the use of blame avoidance strategies for retrenchment purposes in various settings and have explored the conditions under which officeholders can successfully apply such strategies (Vis, 2009;Giger and Nelson, 2011;Wenzelburger, 2011;Mortensen, 2012;Jensen and Mortensen, 2014;Wenzelburger, 2014;Vis, 2016;Hinterleitner et al, 2016;Sager and Hinterleitner, 2016).…”
Section: Four Worlds Of Blame Avoidancementioning
confidence: 99%
“…Within this study, being exploratory in nature, the 'complex' (derived without the use of remainders) and 'parsimonious' (derived with the use of remainders) solutions are considered. This approach is advocated by Wagemann and Schneider (2010), who state that both the complex and parsimonious solutions should be exposited in a fsQCA analysis (see also Vis, 2009). …”
Section: Fsqca Analysismentioning
confidence: 99%
“…Building on the classical debate on whether leftist and rightist parties play different roles in welfare state reforms (e.g. Iversen and Cusack, 2000;Huber and Stephens, 2001;Korpi and Palme, 2003), recent research has shown that the effect of political parties is conditional on socio-economic conditions (Vis, 2009;Jensen, 2012). We show that the effect of leftwing governments is conditional on socio-economic conditions.…”
Section: List Of Tables and Figuresmentioning
confidence: 59%
“…Persistently high levels of joblessness lead to high expenditures on unemployed benefits and therefore to budgetary stress, regardless of the colour of the government (Saint-Paul 1996, Gaston andRajaguru 2008). Indeed, relying on fuzzy set qualitative analysis, Vis (2009) found that deteriorating economic situations trigger cuts in unemployment benefits by both rightist and leftist governments. However, this does not imply that partisan differences do not matter.…”
Section: Partisan Politicsmentioning
confidence: 99%